Trends and Associated Factors of Under-five Mortality Based on 2008-2016 Data in Kersa Health and Demographic Surveillance Site, Eastern Ethiopia - Gebisa Dirirsa Gutema MPH; Abraham Geremew PhD; Dechasa Adare Mengistu MSc; Yohannes Mulugeta Dammu MPH; Kefelegn Bayu MSc (SAGE Publishing, 2022)
Background : Of the 6.2 million estimated deaths of children under 15 years of age globally, the death toll of children under 5 years of age accounted for 5.3 million. In Ethiopia, even though significant progress has been made, facility-based research shows that the mortality rate of children under 5 is still high. In the country, particularly in the eastern part, evidence on trends in under-five mortality and associated factors from population-based longitudinal data is limited. Objective : The objective of the study was to assess under-five mortality focusing on the trends and associated factors based on 2008-2016 data in Kersa Health and Demographic Surveillance Site, Eastern Ethiopia. The method : The study was based on 9 years of surveillance data. The surveillance site was founded in 2007 with the aim of producing community-based health and demographic data in the eastern Ethiopia. Data were collected from the surveillance site and analyzed with STATA version 15 (for factor analysis) and/or Statistical Package for Social Sciences (SPSS) version 26 (for trend analysis) and Microsoft (MS) Excel software. The autoregressive integrated moving average (ARIMA) model and Mann-Kendall were used to analyze mortality trends. Multi-level logistic regression was used to assess the associated factors. Result : There were a total of 18 759 newborns in the surveillance sites, of which 1602 died of children under 5 years of age, and the total mortality rate for children under 5 years of age was 85 per 1000 live births. Trend analysis shows that the mortality rate of children under 5 has been steadily declining during the study period. Multi-level logistic regression shows that the variance of the random component model related to the intercept term is statistically significant, which means that there is a change in the mortality rate of children under 5 between the survey years, which is explained by the random intercept term. Antenatal care visits by mothers (AOR = .61, 95% CI = .49, .74), primary education (AOR = .58, 95% CI = .49, .68), normal birth weight (AOR = .78, 95% CI = .64, .95), and having 2 or fewer total births (AOR = .37, 95% CI = .22, .37) were all associated with child death. Conclusion : Despite the downward trend, the mortality rate of children under 5 years old at the surveillance sites is high. Effective intervention measures should be implemented.